A Deweyan Critique of the Critical Thinking versus Character Education Debate - Axtell, Guy (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2024)
What distinguishes the philosophies of education advanced by pragmatists? Does pragmatism have something distinctive to offer contemporary philosophy of education? This paper applies these questions, which Randall Curren asks in “Pragmatist Philosophy of Education” (2009), to a more specific current debate in philosophy of education: the debate over educating for critical thinking, and/or for intellectual virtues. Which, if either, should be given priority in higher education, and why? This paper develops a Deweyan approach to these questions, inviting character content but also offering specific ways for educators and institutions to stay alert to the pedagogical and indoctrination concerns with character education initiatives, including those for intellectual virtues specifically.